GEOSPATIAL ASPECT OF THE LAND BORDER BETWEEN INDONESIA AND TIMOR-LESTE - Handoyo, Sri (Badan Informasi Geospasial, 2011)
Indonesia has international land borders with three neighboring countries, including the land border with Timor-Leste. The establishment of the international land boundary between Indonesia and Timor-Leste was agreed by the two Governments, the Republic of Indonesia (RI) and the Democratic Republic of Timor-Leste (RDTL) to be based on the Dutch and Portuguese 1904 Treaty and the 1914 Arbitral Awards. Presently, the joint border survey demarcation have been in progress and achieving of about 96% of the total length of the land border lines. According to the verbal description in the 1904 Treaty the boundaries are defined based on geomorphological features, i.e. the watersheds, rivers, and thalwegs oflarge rivers. All these morphological elements of the border were carefully identified and accurately measured to produce geospatial information about the boundaries. This paper describes how the geospatial information along the border lines were measured and fixed.Keywords: Geospatial Information; International Land Boundary; Indonesia and Timor-Leste; Delineation and Demarcation Surveys.ABSTRAKIndonesia memiliki perbatasan darat internasional dengan tiga negara tetangga, termasuk perbatasan darat dengan Timor-Leste. Pembentukan batas darat internasional antara Indonesia dan Timor-Leste disepakati oleh kedua pemerintah, Republik Indonesia (RI) dan Republik Demokratik Timor-Leste (RDTL) didasarkan pada Perjanjian Belanda dan Portugis 1904 dan Penghargaan Arbitrase 1914. Saat ini, survei demarkasi perbatasan bersama terus berlangsung dan telah mencapai sekitar 96% dari total panjang garis perbatasan darat. Menurut deskripsi verbal dalam Perjanjian tahun 1904 batas tersebut didefinisikan berdasarkan unsur geomorfologi, yaitu daerah aliran sungai, sungai, dan thalwegs sungai besar. Semua elemen morfologi perbatasan diidentifikasi dengan cermat dan diukur secara akurat untuk menghasilkan informasi geospasial tentang perbatasan. Makalah ini menggambarkan bagaimana informasi geospasial di sepanjang garis perbatasan diukur dan ditetapkan.Kata Kunci: Informasi Geospasial; Batas Darat Internasional; Indonesia dan Timor-Leste; Survei Delineasi dan Demarkasi.